2010
DOI: 10.1111/j.1360-0443.2009.02688.x
|View full text |Cite
|
Sign up to set email alerts
|

The alcohol industry and public interest science

Abstract: Growing evidence from the tobacco, pharmaceutical and medical fields suggests that financial interests of researchers may compromise their professional judgement and lead to research results that are biased in favour of commercial interests. It is recommended that the integrity of alcohol science is best served if all financial relationships with the alcoholic beverage industry are avoided. In cases where research funding, consulting, writing assignments and other activities are initiated, institutions, indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…A core concern of the research community relates to the reasons why alcohol industry actors are involved in science 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Attention has been consistently drawn to the legitimation and public relations benefits of industry involvements in science.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A core concern of the research community relates to the reasons why alcohol industry actors are involved in science 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Attention has been consistently drawn to the legitimation and public relations benefits of industry involvements in science.…”
Section: Resultsmentioning
confidence: 99%
“…Babor 20 provided an example of the chief executive of a global alcohol producer articulating a strategic motivation for providing research funding to a university (in a speech to an industry group reported in a national newspaper):

‘ He [the chief executive] said the company did not want problems with binge drinking to lead governments to place higher taxes on its products and thus eat into revenues. The UCD [an Irish university] research funding is thus the perfect example of “enlightened self‐interest ”’ 20.

It has been widely suggested that there is an inherent conflict of interest between the commercial goals of industry actors and the production and dissemination of public health research 2, 3, 16, 21, 26, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41. This arises because such research may provide evidence of the harms caused by the industry's products and practices 17, 26.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stenius & Babor point to studies from the wider scientific literature showing that, overall, publications arising from industry funded research are more likely to produce pro-industry results [1]; they are also more likely to use study designs that favour the industry intervention, e.g. [10,11].…”
mentioning
confidence: 99%